ANALISIS WACANA PEMINDAHAN IBU KOTA NEGARA INDONESIA DI MEDIA ONLINE TEMPO - miragi, anton sastra; Sholihul, Sholihul Abidin (LPPM Universitas Putera Batam, 2022)
The purpose of this research is to see how the structure of the text conveyed by the online magazine Tempo to the general public (the public) regarding the discourse on the development of the Indonesian national capital in North Penajam Paser. The Capital City of the Archipelago which will be built carries the concept of Green City, namely the Principle of Designing According to Natural Conditions prioritizing green areas in the central government area using the Vand Djik Analysis text which consists of social cognition and social context. which was conveyed in the 12th edition of the online magazine tempo with the title of gambling using Sri's money, qualitative research using a qualitative descriptive approach. development of the nation's capital, starting with the initial title of the news which seems to be equated with a bet on the initial budget target planned for the breakdown of the situation of the use of APBN funds to be usedThis is the main focus that the online magazine wants to convey. The mass media is considered capable of creating reality because the mass media is able to instruct an event that is reported on